Modified Broucherie: An alternative to preserve bamboo in theEcuadorian Amazon - Jaramillo Benavides1, Andrea Salomé (2024)
The goal this research was to design and build a modifiedBoucherie-type device for the preservation of bamboo, withcharacteristics of transportability and affordable cost thatallows horizontal technological transfer to communities in theEcuadorian Amazon region. The design of the virtual prototypewas carried out through a prescriptive methodology, using3D modeling software that then facilitated the preparation ofthe list of materials and tools necessary for its assembly; Theprototype was developed with materials available in the area;Subsequently, performance tests were carried out on differentbamboo culms. As a result, a device was obtained for preservingbamboo with the modified Boucherie method, which canbe transported with all its components, be used even whenelectricity is not available and whose operation was testedwith bamboo culms of the Dendrocalamus asper species. andGuadua angustifolia Kunth.